Mode of birth and maternal depression/severe anxiety: Findings from Millennium Cohort Study - Elizabeth O. Bodunde; Fergus P. McCarthy; Karen O’connor; Karen Matvienko-Sikar; Ali S. Khashan (PLoS ONE, 2025)
Introduction Limited evidence exists on the association between mode of birth and long-term depression and/or severe anxiety in mothers. We aimed to examine the association between mode of birth and depression and/or severe anxiety by 14 years postpartum. Methods We used data from the Millennium Cohort Study. Data on mode of birth were collected when mothers were 9 months postpartum, and categorized as spontaneous vaginal birth (VB), assisted VB, induced VB, emergency cesarean section (CS), planned CS, and CS after induction. Depression/severe anxiety were collected as one variable and self reported by mothers at 9 months, 3, 5, 7, 11, and 14 years postpartum based on a doctor diagnosis. The primary outcome measure was a diagnosis of depression/severe anxiety up to 14 years postpartum. We used multivariable logistic regression models to estimate crude and adjusted odds ratios (OR) for the association between mode of birth and depression/severe anxiety by 14 years postpartum. Results There were 10,507 singleton mothers included in our analyses. Fully adjusted odds ratio (aOR)for the association between mode of birth and depression/severe anxiety by 14 years postpartum was induced VB, (aOR, 1.13 [95% CI], 1.01–2.28), assisted VB (aOR, 1.03 [95% CI], 0.89–1.19), Emergency CS, (aOR, 1.08 [95% CI], 0.92–1.27), planned CS (aOR, 1.09 [95% CI], 0.93–1.27), and CS after induction (aOR, 1.08 [95% CI], 0.91–1.28). Fully adjusted models did not report any significant association between mode of birth and depression/severe anxiety at other postpartum time points. Conclusions The present findings provide support for association between induction of labor and the risk of long-term depression/severe anxiety by 14 years postpartum. The findings provide no evidence to support association between other modes of birth and maternal depression/anxiety.